Spiritual Values Learning Through History and Archeaology in Egypt - Helmawati Helmawati (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2017)
Learning is a core in educational process. In the process of education, spiritual values can be implemented through various method in the class interaction to improve spiritual belief of students. One of subject material in curriculum which can be implemented to grow and to improve spiritual values is history and archaeology. To listen story, to read it, and to come to visit and observe the history places such as in Egypt gives strengthen sense of spiritual to human kind. For instance, there are lot of historical places spread out in Egypt which can be grow and improve the sense of someone spirituality, i.e. story of Pharaohs, which explained the journey of Moses in the Qur’an. The existence of Nile river, Cairo and Giza, the mosque of Amr bin Ash story, and some other places in Egypt gives spiritual history from ancient time. The spiritual values are also included in aim main goal of Islamic education and The National Educational Goal of Indonesia. In the holly Qur’an, Allah says many stories to be taken the lesson as the guidance to the right and safe ways. In university level, the students who have enough in psychologically and age to go around the world can see directly and observe the place the histories are happened. So, the focus of the article is how to build and growth the spiritual values in someone personality through strategy of learning in historical subject matter. Data were collected through observation to the place where the histories are happened and using NLP (neuro-linguistic programing) as communication strategy as well, interviews and documentary study. Data were analyzed qualitatively. The result of this article is through history and archaeology, people can take the lessons to grow their belief and faith to Allah. To have faith in one God, to struggle in right way, to be patient facing the trial of life, to have critical intelligence, are as some of the spiritual values stated.